Malaria due to Plasmodium falciparum. Presentation of an imported case - Sahily de la Caridad Ortega Medina; Sonia Monteagudo Díaz; Yoelvis Castro Bruzón; Idalmis Reyes Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Malaria is the most frequent tropical infectious disease in the world and depending on the Plasmodium subtype it may be defined its geographical distribution. The number of imported cases in the last years has increased due to the augmentation of the number of travelers from endemic zones, lack of adequate prophylaxis an the prevalence of each time higher of parasites resistant to the drugs used for their treatment. For these reasons a case of acute febrile syndrome is presented and antecedent of having arrived from Angola, country where Malaria is considered endemic and he was diagnosed malaria produced by Plasmodium falciparum. The control of imported malaria is really necessary for the risk it represents on the receptive areas which, as in Cuba, have eliminated the disease.